Bacterial colonization of Intrauterine Device samples from patients without a history of Pelvic Inflammatory Disease (Annals of Medical Research, 2021)
Aim: In this research, we aim to evaluate microbiological colonization of intrauterine devices (IUDs) in patients without the diagnosis of Pelvic Inflammatory Disease (PID) whether it has relationship with the duration of IUD usage. Material and Methods: Our study included patients at the Obstetrics and Gynecology Polyclinic of second degree state hospital between January 1, 2015 and January 1, 2016, who requested the removal of an IUD. A total of 176 patients were recruited for our study. Age, parity, and duration of IUD use were recorded for all patients, who sought treatment at the outpatient clinic. None of the patients had a clinical or laboratory finding of PID. IUD samples, which were collected in the sterile containers, were sent to the microbiology laboratory.Results: The mean age of the patients recruited in our study was 34.5 years. 36 IUD cultures (20.4%) were positive. There were no statistically significant differences between the groups of patients with microorganisms cultured and those with none of the microorganisms cultured; in terms of age, parity, and duration of IUD use.Conclusion: In this study, aerobic bacterial growth occurred in 36 patients, 20.4% of the cultures of the IUDs. In addition, our study adds data to the literature, with the statistical analysis of the groups comparing age, parity, and the duration of IUD use with positive and negative cultures of microorganisms in the IUD samples, as was not done in previous studies.
Keywords: Bacterial colonization; contraception; IUD; PID